2007
DOI: 10.1525/mp.2007.25.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Ornamentation in Performances of a Handel Sonata

Abstract: Ornamentation is one aspect of music associated with emotional affect in Baroque music. In an empirical study, the relationship between ornamentation and emotion was investigated by asking a violinist and flutist to ornament three melodies in different ways to express four emotions: happiness, sadness, love, and anger. The performers adapted the type of ornaments to the instructed emotion as well as the characteristics of the ornaments. The flutist specifically varied the duration, timing, and complexity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…Ashley, 2017) and the limitations of music notation, musicians must interpret a musical work to give a meaningful and expressive performance. Empirical research has demonstrated that musicians employ expressive devices, such as articulation, dynamics, tempo, timing, and ornamentation, to communicate their interpretation of the musical structure (e.g., Sloboda, 1983;Clarke, 1988;Palmer, 1996Palmer, , 1997 and character (e.g., Gabrielsson and Juslin, 1996;Gabrielsson, 1999;Timmers and Ashley, 2007). For this study we define an expressive music performance as a performance in which the musician communicates their interpretation of the compositional structure and musical character of a work convincingly to a listener (Meissner, 2018;.…”
Section: Working Definitionsmentioning
confidence: 99%
“…Ashley, 2017) and the limitations of music notation, musicians must interpret a musical work to give a meaningful and expressive performance. Empirical research has demonstrated that musicians employ expressive devices, such as articulation, dynamics, tempo, timing, and ornamentation, to communicate their interpretation of the musical structure (e.g., Sloboda, 1983;Clarke, 1988;Palmer, 1996Palmer, , 1997 and character (e.g., Gabrielsson and Juslin, 1996;Gabrielsson, 1999;Timmers and Ashley, 2007). For this study we define an expressive music performance as a performance in which the musician communicates their interpretation of the compositional structure and musical character of a work convincingly to a listener (Meissner, 2018;.…”
Section: Working Definitionsmentioning
confidence: 99%
“…To express emotions the musician modifies various auditory cues, like tempo, timing, articulation, dynamics, timbre, attack, decay (Juslin & Persson, 2002), intonation (Johnson, 2004), vibrato (Juslin et al, 2004), ornamentation (Timmers & Ashley, 2007) and ancillary gestures 2 (Davidson, 1993(Davidson, , 2005Davidson & Correia, 2002;Dahl & Friberg, 2007;Wanderley & Vines, 2006). Cue utilization varies among performers, instruments and musical styles (Juslin & Timmers, 2010).…”
Section: International Journal Of Music Education Imentioning
confidence: 99%
“…Emotional Expression , which serves to convey emotions to listeners, is often seen as the most important element of expressive performance (Juslin, 2003; Juslin et al, 2004). To express emotions the musician modifies various auditory cues, like tempo, timing, articulation, dynamics, timbre, attack, decay (Juslin & Persson, 2002), intonation (Johnson, 2004), vibrato (Juslin et al, 2004), ornamentation (Timmers & Ashley, 2007) and ancillary gestures 2 (Dahl & Friberg, 2007; Davidson, 1993, 2005; Davidson & Correia, 2002; Wanderley & Vines, 2006). Cue utilization varies among performers, instruments and musical styles (Juslin & Timmers, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Music theory involves frequent references to tonal or harmonic motion (Lerdahl and Krumhansl, 2007), even gravitational forces between tones and chords (Larson and Van Handel, 2005), which can create “tension,” “release,” “climax,” “repose,” and “relaxation.” Although Meyer's (1956) well-known theory focused primarily on how the thwarting of musical expectations might arouse emotion in listeners, it seems likely that this internal play within the musical structure could also affect perceived emotions (e.g., the emotional intensity; see Sloboda and Lehmann, 2001; Timmers and Ashley, 2007, for examples). Intrinsic sources of musical expression in music have rarely been investigated thus far, but they are unlikely to express specific emotions by themselves.…”
Section: How Does Music Express Emotions? Three Types Of Codingmentioning
confidence: 99%